On the Risk of a Sovereign Debt Crisis in Italy - Oliver Holtemöller; Tobias Knedlik; Axel Lindner (Intereconomics, 2018)
The intention for the Italian government to stimulate business activity via large increases in government spending is not in line with the stabilisation of the public debt ratio. Instead, if such policy were implemented, the risk of a sovereign debt crisis would be high. In this article, we analyse the capacity of the Italian economy to shoulder sovereign debt under different scenarios. We conclude that focusing on growth enhancing structural reforms, would allow for moderate increases in public expenditure.
Keywords: 330